Biochemical Mechanism of Modulation of Human P-glycoprotein by Stemofoline - Chanmahasathien W. (2014)
The resistance to chemotherapeutic drugs by cancer cells is considered to be one of the major obstacles for success in the treatment of cancer. A major mechanism underlying this multidrug resistance is the overexpression of P-glycoprotein (P-gp), resulting in insufficient drug delivery to the tumor sites. A previous study has shown that stemofoline, an alkaloid isolated from Stemona burkillii, could enhance the sensitivity of chemotherapeutics in a synergistic fashion. In the present study, we have focused on the effect of stemofoline on the modulation of P-gp function in a multidrug resistant human cervical carcinoma cell line (KB-V1). The effects of stemofoline on a radiolabeled drug, [3H]-vinblastine, and fluorescent P-gp substrates, rhodamine 123 and calcein-AM accumulation or retention were investigated to confirm this finding. Stemofoline could increase the accumulation or retention of radiolabeled drugs or fluorescent P-gp substrates in a dose-dependent manner. For additional studies on drug-P-gp binding, P-gp ATPase activity was stimulated by stemofoline in a concentration-dependent manner. More evidence was offered that stemofoline inhibits the effect on photoaffinity labeling of P-gp with [125I]-iodoarylazidoprazosin in a concentration-dependent manner. These data indicate that stemofoline may interact directly with P-gp and inhibit P-gp activity, whereas stemofoline has no effect on P-gp expression. Taken together, the results exhibit that stemofoline possesses an effective MDR modulator, and may be used in combination with conventional chemotherapeutic drugs to reverse MDR in cancer cells. © Georg Thieme Verlag KG.